PRODUCTIVE PERFORMANCES OF SWAMP BUFFALOES OF ASSAM - ISLAM, S.; GOGOI, A.K.; SAIKIA, J.K.; SAHARIA, J.; GOHAIN, A. (Indian Journal of Animal Production and Management, 2017)
ABSTRACTA survey was carried out to study productive performances of swamp buffaloes ofAssam. Average lactation length, lactation milk yield, peak yield, and days to attain peak yieldwere found to be 237.06 ± 0.74 days, 448.38 ± 1.67 kg, 3.41 ± 0.02 kg and 54.16 ± 0.19 daysrespectively. Lactation length was found to be affected significantly by type of animal, locationand season of calving while lactation order exerted non significant effect. Lactation milk yieldand peak yield was found to be affected significantly by type of animal, location, lactation orderand season of calving. Days to attain peak yield was found to be affected significantly only byseason of calving while location, type of animal, lactation order exerted non significant effect.Key words : Swamp buffalo, Assam, Productive traits